An EFQM excellence model for integrated healthcare governance. Issue 2 (9th March 2015) - Favaretti, Carlo; De Pieri, Paolo; Torri, Emanuele; Guarrera, Giovanni; Fontana, Fabrizio; Debiasi, Franco; Flor, Luciano
Abstract : Purpose: – The purpose of this paper is to account for a ten-year experience with the European Foundation for Quality Management (EFQM) Excellence Model implemented in the Trento Healthcare Trust. Design/methodology/approach: – Since 2000, the EFQM Excellence Model provided an overarching framework to streamline business process governance, to support and improve its enablers and results. From 2000 to 2009, staff performed four internal (self) and four external EFQM-based assessments that provided guidance for an integrated management system. Over the years, key controls and assurances improved service quality through business planning, learning and practice cycles. Findings: – Rising assessment ratings and improving results characterized the journey. The average self-assessment score (on a 1, 000 points scale) was 290 in 2001, which increased to 610 in 2008. Since 2006, the Trust has been Recognized for Excellence (four stars). The organization improved significantly on customer satisfaction, people results and key service delivery and outcomes. Practical implications: – The EFQM Model can act as an effective tool to meet governance demands and promote system-level results. The approach to integrated governance discussed here may support similar change processes in comparable organizations. Originality/value: – The paper describes a unique experience when implementing EFQM within a large Italian healthcare system, which had a broader reach and lasted longer than any experience in Italian healthcare.